Portable Electrochemiluminescence Platform With Laser-Induced Graphene-Based U-Shaped Bipolar Electrode for Selective Sensing of Various Analytes - Bhaiyya, Manish; Pattnaik, Prasant Kumar; Goel, Sanket (IEEE transactions on electron devices, 2021)
In recent years, rising need of microfluidics-based point-of-care devices has led to cost-effective solutions at or near the location of patients. With this motivation, herein, laser-induced graphene (LIG)-based electrochemiluminescence (ECL) system loaded with U-shaped bipolar electrode (U-BPE) has been developed and its application for enzymeless sensing of various biomarkers has been validated. Low-cost and easily available flexible polyimide (PI) sheet has been effectively used for the fabrication of LIG U-BPE ECL device. With optimized speed and power, the ablation of CO 2 laser on PI has been carried out to create graphenized driving electrodes and U-BPE in a single step. A cost-effective and portable 3-D printed platform has been developed for image sensing of ECL signals. The bulky power supply was effectively replaced by a dual-functional android smartphone to provide power to the LIG U-BPE ECL sensor and to capture the ECL signals. With this mini-platform, determination of various analytes, such as H 2 O 2 , D-glucose, lactate, and choline, has been accomplished in a linear range of 0.1-50, 0.1-70, 1-100, and 1- 100~μ \text{M} with limit of detection (LOD) of 4.36, 2.51, 5.32, and 4.01~μ \text{M} , respectively. An interference study has been performed and it was found that after adding interfering compounds in analytes, ECL signal intensity was reduced to less than 5%. Hence, it was proven that LIG U-BPE ECL device was very selective to different analytes concerning to their voltages.